Nilai-Nilai Pendidikan Islam Yang Terdapat Pada Mandi Taman Di Pulau Merbau - Siti Rohayati; Sumira Sumira; Tuti Nuriyati (Sekolah Tinggi Agama Islam Yayasan Pendidikan Ilmu Qur'an Baubau, 2023)
This study aims to identify the Islamic education values found in the Taman Mandi activity in Pulau Merbau and their implementation in daily life. The research method used is qualitative with observation and interview techniques with Taman Mandi participants in Pulau Merbau. The results of the study indicate that there are Islamic education values such as rahmatan lil alamin, tawakal, gratitude, cleanliness, balance, and environmental care in Taman Mandi activity in Pulau Merbau. The implementation of these Islamic education values can be carried out in daily life through attitudes such as maintaining environmental cleanliness, expressing gratitude and thankfulness for the blessings received, and maintaining balance in all aspects of life.